Diversity and activity of amylase-producing bacteria isolated from mangrove soil in Thailand (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Klinfoong R, Thummakasorn C, Ungwiwatkul S, Boontanom P, Chantarasiri A. 2022. Diversity and activity of amylase-producing bacteria isolated from mangrove soil in Thailand. Biodiversitas 23: 5519-5531. Mangrove forests are a potential ecosystem for the isolation of various economic enzymes derived from mangrove-associated bacteria. The knowledge of amylase-producing bacteria isolated from mangrove forests in the Southeast Asian region has been scarce. This study aimed to investigate the isolation, genetic identification, and activity characterization of amylase-producing bacteria from mangrove soils in Thailand. The amylase-producing bacteria isolated from mangrove soils in the present were genetically belong to the genera Bacillus, Desulfurella, Peribacillus, Priestia, and Pseudomonas. Several amylase-producing bacteria such as Bacillus proteolyticus, Desulfurella, Pseudomonas entomophila, and Pseudomonas putida found in this study have hardly ever been reported. The Bacillus paralicheniformis strain DNP0507 was the most active amylolytic bacterium with 2.395 ± 0.133 U/mg of amylase activity. The optimum temperature and pH for amylolytic activity were determined to be 50°C at a pH of 7.0 with a thermal stability range of 20-60°C at a neutral pH of 7.0-8.0. The enzyme activity was significantly enhanced by Cu2+, Co2+, and Pb2+ and was inhibited considerably by a chelating agent EDTA. Finally, the most active amylolytic B. paralicheniformis strain DNP0507 could be applied in baking industries, food industries, and starchy waste valorization.
Keywords: Amylase, amylolytic activity, Bacillus paralicheniformis, mangrove soil, Thailand